An integrated framework for designing formulated products. (5th December 2017) - Zhang, Lei; Fung, Ka Yip; Zhang, Xiang; Fung, Ho Ki; Ng, Ka Ming
Highlights: An integrated framework is proposed for all kinds of formulated products. Generic design steps are given for the design of formulated products. Strategy of design methods (such as experience, database, rule-based methods, and model-based methods) is given. A multi-layer knowledge library is established to store all the information for designing formulated products. Abstract: Formulated products are created by mixing various ingredients together. They are commercially produced for drugs, cosmetics, cleaning agents, lubricants and many others. The design of formulated products is diverse and multidisciplinary in nature; physico-chemical properties, product microstructure, product quality, and all other related areas have to be considered integratively. Various types of data, methods and tools are needed to tackle formulated product design problems to achieve an optimal design. In this study, an integrated framework as well as the design steps are proposed for the design of all kinds of formulated products including liquids, solids, emulsions, etc. Strategies for the selection of different modelling methods such as rule-based methods, model-based methods, experiments and databases are also presented. A multi-layer knowledge library is proposed to store all the information needed in the design of formulated products. Case studies of battery electrolyte and laundry detergent are given to illustrate the design framework.